Role of Colour and Spectral Doppler in the Diagnosis of Intra Uterine Growth Restriction (IUGR) and its Prediction of Adverse Perinatal Outcome - Manash Kumar Bora; Kaveri Sharma; B.P Venkatesh; Uppin Shivanna; Usha Jayagurunathan; Vijay Karthik Jagan (JCDR Research and Publications Pvt. Ltd., 2015)
Introduction and Aim: The aim of this study was to evaluate the diagnostic accuracy of the pulsatility index (PI) and resistive index (RI) in umbilical artery (UA) and middle cerebral artery (MCA) in the diagnosis of IUGR and its role in averting or minimising adverse perinatal outcome. Materials and Methods: A total of 100 cases of clinically suspected IUGR were enrolled in to the study. The patient usually had an adverse factor in the current or previous pregnancy which was a contributing factor for developing Intra Uterine Growth Restriction (IUGR). All such cases underwent colour and spectral Doppler between 28 to 30 weeks in serial intervals and till delivery. Standardized cut off values were taken from previous studies for the data analysis. Diagnostic accuracy of Doppler indices for prediction of IUGR was done by assessing the newborn parameters for growth restriction and perinatal outcome. Results: For UA PI overall diagnostic accuracy was higher at 70% and UA RI at 54%. For MCA overall diagnostic accuracy of PI was 76.6% and for RI, it was marginally low at 70.3%. In both the vessels the PI was having higher sensitivity and specificity from an early gestational age (GA). Further the sensitivity and specificity increased for both vessels with advancing GA. Conclusion: We conclude that colour and spectral Doppler is an effective and non invasive tool which can predict and detect the cases of IUGR early in gestation and help in timely management thereby producing a favourable perinatal outcome.